Pengembangan UMKM Melalui Strategi Pemasaran di Era Digitalisasi di Desa Cibunar Kecamatan Rancakalong Kabupaten Sumedang - Purwanti, Neli; Solihin, Budi (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The development of MSMEs through the implementation of marketing strategies in the digitalization era has become a major concern in improving the competitiveness and performance of MSMEs in the current digitalization era. This study documents the strategic approach applied to empower MSMEs in Cibunar Village, Rancakalong, Sumedang, through a Community Service (PKM) program that focuses on training and mentoring in marketing in the digitalization era. In this study, various challenges and opportunities faced by MSMEs in Cibunar Village were analyzed in depth, including limited knowledge and skills in marketing in the digitalization era, access to internet infrastructure, and practical obstacles in managing social media and e-commerce platforms. Through a series of PKM activities, MSME players were provided with training on marketing strategies in the digitalization era, social media management, and e-commerce. The implementation evaluation showed significant improvements in participants' understanding and skills, as well as positive responses to the PKM activities. This research makes an important contribution to the practical understanding of the implementation of marketing strategies in the digitalization era for MSMEs in Cibunar Village.